UŻYWANIE DRONÓW W CELU ZWALCZANIA TERRORYZMU ŚWIETLE ‘IUS AD BELLUM’ - Kułaga, Łukasz (Zeszyty Prawnicze, 2016)
The Use of Drones in Combating International Terrorism from the Perspective of ‘ius ad bellum’ Summary The increasing practice of using armed unmanned aerial vehicles (military UAVs, commonly known as drones) by some countries to eliminate suspected terrorists raises a number of controversies from the perspective of international law. These controversies are also related to the specific features of military UAVs, which make it possible to kill targeted individuals without risk to the military personnel of the country concerned, and thereby may encourage the abusive interpretation of the applicable legal regulations. This article discusses these issues from the perspective of ius ad bellum, in particular the right to self-defence. It shows the main controversial points on the scope of invoking the right to self-defence in such cases, in particular the possibility of invoking the right to self-defence in response to an attack by a non-state entity, the question of pre-emptive self-defence, the importance of the severity of the force used as a condition allowing for the use of force in self-defence, and the relevance of the principles of proportionality and necessity. The article also presents an outline of the vast and highly controversial issues associated with the definition of terrorism from the point of view of international law.